(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
The purpose of this study was to find out the process of traditional Bima wedding customs and Tthe meaning of process traditional wedding in Bima society. This research method uses a qualitative descriptive method, this method is intended to describe the process of traditional marriage customs and the meaning of the traditional wedding process in Panda Village, Palibelo District, Bima Regency.The results of the research obtained directly from several sources indicate that the traditional customary marriage process in Bima, West Nusa Tenggara, is still very culturally attached and will continue to be preserved by the people of Bima. The results showed that in the district of Bima, especially in the customary marriage, there were 14 processes, namely: Nari Ro Mpida (private visit), Katada Nggahi (belongis), Pita Nggahi (reassure promise), Sodi Dou (engagement), Panati (proposed), Ngge ’e Nuru (dedication), Mbolo Weki (deliberation), Teka Ra Ne’e (bring the present), Wa’a Co’i (bring dowry), Peta Kapanca (henna and dzikir), Weha Nggahi (asking for the blessing of parents), Boho Oi Ndeu (single release shower), Lafa (ijab qabul), Pamaco (guaride).